PENGEMBANGAN PEMBELAJARAN DARING MATERI BANGUN RUANG SISI DATAR MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN WHATSAPP DAN ANIMASI GIF ANDROID - Adi Rustandi; Martin Bernard; Arif Sunaryo (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this research is to find out how to develop mathematics teaching materials on flat-sided space using Whatsapp and Android Gif Animations using the Scientific method that is aligned with the Covid 19 conditions. The development of this online learning media is through the validation stage of material experts and media experts. The subject of the trial was carried out on class VIII students at Mts PPI 88 Melong, Cimahi City. This learning media has been validated on material experts with an average score of 4.2 on the "good" eligibility criteria, and on media experts with an average score of 3.95 on the "good" eligibility criteria and was tested on small and large scale classes in Mts PPI 88 Melong Cimahi City.